Integrated UPLC–MS/MS and UPLC–Q–TOF–MS/MS analysis to reveal pharmacokinetics, tissue distribution, metabolism, and excretion of sipeimine in rats - Zong, Hui; Wang, Chongyang; He, Dongdong; Liu, Liting; Wan, Juanjuan; Wang, Guodong; Li, Dingtao; Ran, Jun; Zhang, Meiling; Tang, Hui; Wang, Liping (Frontiers in Pharmacology, 2025)
Background and ObjectiveFritillaria Bulbus is a traditional Chinese medicine used to treat respiratory diseases such as cough, expectoration, and asthma for more than 2000 years. Sipeimine, a major isosteroidal alkaloid isolated from Fritillaria Bulbus, has attracted considerable attention from the research community owing to its antitussive, anti-inflammatory, and lung-protective activities. However, there exist few reports regarding the in vivo disposition of sipeimine. This study aims to investigate the disposition of sipeimine in rats.MethodsA rapid, sensitive, and selective UPLC–MS/MS approach was developed to the quantification of sipeimine in various biological samples and successfully applied to the investigation of pharmacokinetic characteristics, tissue distribution, and excretion of sipeimine in rats. A reliable UPLC–Q–TOF–MS/MS combined with a scientific metabolite identification strategy was used to characterize the metabolic transformation of sipeimine in rat plasma and urine.ResultsThe established UPLC–MS/MS method was accurate and reliable with a good linearity (r2 > 0.99) in the respective concentration range, satisfying the quantitative requirements. Sipeimine exhibited the characteristics of rapid absorption and slow elimination in rats, with an average oral bioavailability of 40%. Furthermore, sipeimine was rapidly distributed in all the organs except brain, and the plasma protein binding ratio of sipeimine was found to be approximately 30%. The metabolism of sipeimine in rats is chiefly accomplished via its hydroxylation, sulfation, and glucose conjugation. Analysis of fecal and urinary samples revealed that sipeimine is predominantly excreted unchanged via renal elimination.ConclusionThe pharmacokinetics, tissue distribution, metabolism, and excretion of sipeimine were comprehensively characterized and elucidated. These results are expected to prove useful for the interpretation of the pharmacokinetic and pharmacodynamic characteristics of sipeimine and the traditional Chinese medicines containing sipeimine.